Consumer Legal Protection in the Perspective Of The Standard Clause In Tinujau In The Consumer Protection Law In The City Of Ternate - Rusdin Alauddin; Irham Rosyidi; Abdul Azis; Nurhadija Isa (LEGAL BRIEF, 2022)
This study aims to determine the inclusion of standard clauses in Supermarkets in Ternate City and consumer legal protection related to harmful standard clauses. The type of research used is juridical, a form of legal research that takes sources from library materials. However, empirical research is also needed to find out how to include standard clauses in the field to support juridical research. The study results indicate that so far, the standard clauses contained by business actors, such as supermarkets, are not entirely by the provisions stipulated in the Consumer Protection Act. This is evident from the results of the study that business actors will include unilateral provisions and submission to new or advanced regulations that can occur at any time in the future, for example, adding money or exchanging for other goods when consumers want to insist on exchanging goods that have been purchased and of course waiving the clause. Standards prohibited by the Consumer Protection Act Article 18 paragraph 1 point g. Due to the position of the parties listed in the standard clause, it is considered unbalanced or unequal between the creditor and the customer. Business actors and debtors, in this case, consumers, then are where the role of law is needed to provide legal protection for upholding justice. Therefore, it is necessary to enforce the rights of consumers by the mandate of Law Number 8 of 1999 concerning Consumer Protection Article 4, which regulates consumer rights such as the right to have their opinions and complaints heard on the goods and services used and the right to be treated or treated. Served correctly and honestly, and non-discriminatory. This is necessary for the sake of legal protection for consumers